Virtual resource pricing scheme in cloud platforms. (2018) - Hu, Ying; Xiao, Ze
Recently, economic model has been widely applied in cloud platforms for regulating virtual resource sharing. In the economic model, resource pricing scheme plays a key role for managing the relationship between cloud users and cloud providers. In this paper, we present a novel pricing scheme for virtual resource provision with aiming at improving resource utilisation and reducing operational costs for cloud providers. Unlike previous studies, the proposed pricing scheme applies producer-retailer-client model to describe the procedure of virtual resource trade and provides the optimal pricing solution by using gaming theory. Extensive experiments are conducted in a real-world cloud platform, and the results demonstrate that the proposed pricing scheme outperforms other approaches in terms of the increased profit and the reduction of variance of virtual resource prices.